2020
DOI: 10.18196/jai.2101144
|View full text |Cite
|
Sign up to set email alerts
|

Budgetary Participation, Compensation, and Performance of Local Government Working Unit: The Intervening Role of Organizational Commitment

Abstract: Research aims: This paper aims primarily to investigate the effect of the skills of forensic accountants on the public sector in revealing fraud in Indonesia. Therefore, this research focuses on the investigation of forensic accountants in the public sector. Design/Methodology/Approach: This study employed a quantitative approach with a survey method. Questionnaires were distributed to the auditors possessing experiences to conduct investigative auditing in the Audit Board of the Republik of Indonesia (BPK RI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The framework for thinking about the influence of professionalism and expertise from forensic auditors with competent evidence as intervening variables in disclosing corruption is in line with the results of research from (1) Amsari & Rasibo (2017) 2019) conducted a study on examiners from the Financial Audit Agency with as many as 160 respondents concluding that forensic auditor certification has a positive effect on the auditor's ability to detect fraud; (7) Karim ( 2020) who conducted interviews with 16 accounting practitioners in Bangladesh in fraud prevention and detection matters and stated that there are some essential accounting skills in the profession ; (8) Sumartono et al (2020) conducted research on the BPK special region of Yogyakarta with 44 respondents concluding that business skills have a significant and negative effect on the skills of forensic accountants in uncovering fraud in the public sector; (9) Saleh et al (2020) identified the skills needed for forensic accountants in detecting and combating corrupt practices and financial fraud for 63 professional accountants in the Iraqi Kurdistan region and concluded that techniques using forensic accounting had an impact on detecting and eradicating financial corruption;…”
Section: 3supporting
confidence: 58%
See 1 more Smart Citation
“…The framework for thinking about the influence of professionalism and expertise from forensic auditors with competent evidence as intervening variables in disclosing corruption is in line with the results of research from (1) Amsari & Rasibo (2017) 2019) conducted a study on examiners from the Financial Audit Agency with as many as 160 respondents concluding that forensic auditor certification has a positive effect on the auditor's ability to detect fraud; (7) Karim ( 2020) who conducted interviews with 16 accounting practitioners in Bangladesh in fraud prevention and detection matters and stated that there are some essential accounting skills in the profession ; (8) Sumartono et al (2020) conducted research on the BPK special region of Yogyakarta with 44 respondents concluding that business skills have a significant and negative effect on the skills of forensic accountants in uncovering fraud in the public sector; (9) Saleh et al (2020) identified the skills needed for forensic accountants in detecting and combating corrupt practices and financial fraud for 63 professional accountants in the Iraqi Kurdistan region and concluded that techniques using forensic accounting had an impact on detecting and eradicating financial corruption;…”
Section: 3supporting
confidence: 58%
“…A different matter is shown by Asterini (2018) who concludes that there is no effect of professionalism on disclosing corruption. Likewise with the results of research from Sumartono et al (2020), which states that financial accounting skills do not have a significant impact on the skills of forensic accountants in uncovering fraud in the public sector. Research from Widiyanti (2016), also concluded that the professionalism of the forensic auditor has no significant effect on corruption disclosure.…”
Section: Introductionmentioning
confidence: 80%
“…Forensic accounting is the name given to this branch of accounting. In essence, forensic accounting combines the abilities of an auditor and an investigator (Ijeoma, 2015;Sumartono & Hamdani, 2020;Amasiatu & Okoye, 2023). The primary objective of the forensic accounting profession, according to Howieson (2018), is to support people, organisations, and governments through one of the most hard times by providing a wide range of services that may aid their continuation.…”
Section: Introductionmentioning
confidence: 99%
“…Investigative audits have proven effective in detecting fraud (Briyan & Urumsah, 2019). So that, auditor with investigative skills will have a greater opportunity to uncover fraud (Sumartono et al, 2020).…”
Section: Introductionmentioning
confidence: 99%